PENERAPAN METODE IMLA’ MANZHUR UNTUK MELATIH DAYA INGAT MENULIS BAHASA ARAB SISWA MI IHSANIYAH JAMBI - Hany Khoirani; Friscilla Wulan Tersta; Mar’atun Sholiha; supian.ramli@unja.ac.id (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The imla’ manzhur method is a form of Arabic writing instruction that involves the stages of observing, understanding, memorizing, and independently rewriting. This study was motivated by the low Arabic writing proficiency of fifth-grade students at MI Ihsaniyah in Jambi City, as evidenced by their difficulty in recalling the shapes of the Hijaiyah letters, writing vocabulary correctly, connecting letters, and a lack of precision and confidence in writing. This study aims to examine the implementation of the Imla’ Manzhur method, test its effectiveness in training students’ memory for Arabic writing, and identify the benefits students perceive after the method’s implementation. This study employs the Classroom Action Research method, conducted over two cycles. The research subjects were fifth-grade students at MI Ihsaniyah in Jambi City. Data collection techniques included observation, tests, interviews, and documentation. The results of the study indicate that the implementation of the imla’ manzhur method significantly improves students’ memory for writing Arabic. The learning process was carried out through text observation, group reading, erasing sample text, and rewriting from memory. The improvement in learning outcomes is evident in the students’ average scores, which rose from 39% in the pre-intervention phase to 46% in Cycle I and reached 75% in Cycle II. In addition, 83% of students met the Minimum Passing Criteria (KKM) in Cycle II. The imla’ manzhur method also improved students’ accuracy, concentration, engagement, and self-confidence in learning to write Arabic. Thus, the imla’ manzhur method is effective for training elementary school students’ memory in writing Arabic.